2009
DOI: 10.1016/j.str.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A Role for a Specific Cholesterol Interaction in Stabilizing the Apo Configuration of the Human A 2A Adenosine Receptor

Abstract: SUMMARY The function of G-protein coupled receptors is tightly modulated by the lipid environment. Long timescale molecular dynamics simulations (totaling ~3 microsec) of the A2A receptor in cholesterol-free bilayers, with and without the antagonist ZM241385 bound, demonstrate an instability of helix II in the apo receptor in cholesterol-poor membrane regions. We directly observe that the effect of cholesterol binding is to stabilize helix II against a buckling type deformation, perhaps rationalizing the obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
132
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 42 publications
(75 reference statements)
7
132
1
Order By: Relevance
“…Interestingly, recent molecular dynamics simulations reviewed in ref 36 have shown that membrane cholesterol specifically interacts with transmembrane domains of GPCRs, such as rhodopsin 37 and human A 2A adenosine receptor. 38 In this work, we show that membrane cholesterol binds preferentially to certain sites on the serotonin 1A receptor using multiple long time scale coarse-grain simulations. It should be noted here that the binding of cholesterol to membrane proteins in general and GPCRs in particular is currently being extensively explored and it appears that no consensus model has emerged yet.…”
Section: ■ Discussionmentioning
confidence: 81%
“…Interestingly, recent molecular dynamics simulations reviewed in ref 36 have shown that membrane cholesterol specifically interacts with transmembrane domains of GPCRs, such as rhodopsin 37 and human A 2A adenosine receptor. 38 In this work, we show that membrane cholesterol binds preferentially to certain sites on the serotonin 1A receptor using multiple long time scale coarse-grain simulations. It should be noted here that the binding of cholesterol to membrane proteins in general and GPCRs in particular is currently being extensively explored and it appears that no consensus model has emerged yet.…”
Section: ■ Discussionmentioning
confidence: 81%
“…Cholesterol interaction apparently stabilizes this helix and has been proposed as a possible explanation for the observation that the A 2A receptor couples to G protein only in the presence of cholesterol 37 . Interactions of membrane lipids with ion channels are also of substantial interest 38,39 and could be influenced by membrane demixing effects 39,40 .…”
Section: Membrane Physical Chemistrymentioning
confidence: 98%
“…This observation led to the speculation that the actual lock might be unique to rhodopsin, so although the motif was present in most GPCRs, it cannot actually act as a functional "lock" Rasmussen et al, 2007). This supposition prompted a series of molecular dynamics experiments for each of these receptors, all of which revealed that the ionic lock, even if absent (disrupted) in the crystal structure, quickly reforms once restraints imposed by the T4-lysozyme fusion and crystal lattice are removed (Dror et al, 2009;Lyman et al, 2009;Vanni et al, 2009;Jojart et al, 2010;Romo et al, 2010;Fanelli and Felline, 2011). This does not mean that the observed disruption of the ionic lock is an entirely artificially induced state; partial occupancy of a disrupted ionic lock state might explain the agonist-independent activation observed for these receptors (Fig.…”
Section: The D(e)ry Motif Within G Protein-coupled Receptorsmentioning
confidence: 99%